THE EFFECT OF TAX PLANNING, TUNNELING INCENTIVES AND INTANGIBLE ASSETS ON TRANSFER PRICING BEHAVIOR IN MANUFACTURING COMPANIES THAT HAVE SPECIAL RELATIONSHIPS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2014-2016 PERIOD - Hasan Effendi Jafri; Elia Mustikasari (Berkala Akuntansi dan Keuangan Indonesia, 2018)
This aim of this research is testing effect of tax planning, incentive tunneling and intangible assets to transfer pricing behavior as measured by sales of related parties divided by sales of non-related parties. Tax planning is measured by Cash ETR, incentive tunneling measured by related party parties divided by total assets and intangible assets measured by total intangible assets divided by total sales. The population in this study is a manufacturing company listed on the Indnesia Stock Exchange 2014-2016. Determination of selected sample in research using purposive sampling method. Examination of influence of tax planning, incenntive tunnneling and intangible asset to behavior of transistor pricinng analyzed using softwareSPSS 20.0. The results showed that there were 134 companies meeting the sample criteria. Based on the results of multiple linear regression analysis with 5% significance, the results of this study concluded that: (1) tax planning affect the behavior of transfer pricing (2) incentive tunneling affect the transfer pricing behavior (3) intangible assets have no effect the transfer pricing behavior.